ASSESSMENT OF THE QUALITY OF PEDIATRIC CARDIOPULMONARY RESUSCITATION USING THE IN SITU MOCK CODE TOOL - Kuzma,Gabriela de Sio Puetter (2020)
ABSTRACT Objective: To evaluate the quality of individual and team care for cardiac arrest in a pediatric hospital using clinical surprise simulation (in situ mock code). Methods: We conducted an observational study with a sample of the hospital staff. Clinical simulations of cardiorespiratory arrest were performed in several sectors and work shifts. The mock code occurred in vacant beds of the sector without previous notification to the teams on call. One researcher conducted all mock codes and another evaluated individual and team attendance through a questionnaire contemplating recommendation for adequate cardiopulmonary resuscitation, based on the Pediatric Advanced Life Support (PALS) guidelines. At the end of the simulations, the research team provided a debriefing to the team tested. Results: Fifteen in situ mock code were performed with 56 nursing professionals (including nurses, nursing residents and technicians) and 11 physicians (including two pediatric residents and four residents of pediatric subspecialties). The evaluation showed that 46.7% of the professionals identified cardiac arrest checking for responsiveness (26.7%) and pulse (46.7%); 91.6% requested cardiac monitoring and venous access. In one case (8.3%) the cardiac compression technique was correct in depth and frequency, while 50% performed cardiopulmonary resuscitation correctly regarding the proportion of compressions and ventilation. According to PALS guidelines, the teams had a good performance in the work dynamics. Conclusions: There was low adherence to the PALS guidelines during cardiac arrest simulations. The quality of cardiopulmonary resuscitation should be improved in many points. We suggest periodical clinical simulations in pediatric services to improve cardiopulmonary resuscitation performance.